Smartwatch detected high-degree atrioventricular block requiring pacemaker implantation after transcatheter aortic valve replacement during COVID-19. Issue 3 (8th June 2021) - Fan, Jiaqi; Liu, Xianbao; Xu, Yeming; Xu, Jianguo; Wang, Jian'an
Graphical Abstract: